Upaya SMP Negeri 3 Bancar dalam Menangani dan Mencegah Kasus Bullying - Sukamat Sukamat; Thomas Rico Kurniawan; Yolla Adelina Febrianti; Aftuha Febrianto; Rifky Rizmawan; Hawa Wardani Bunga Cantika; Ahmad Yoga Ebriansyah; Dwi Jhonsen Kurniawan; Ikhsan Aslah Asdiqi; Sutomo Sutomo (Journal Innovation In Education, 2025)
Bullying is one of the most common forms of violence occurring in school environments and has a serious impact on students’ physical and psychological well-being. Despite various government policies promoting child-friendly schools, bullying practices are still frequently found and have not been effectively addressed. This study aims to explore the efforts undertaken by SMP Negeri 3 Bancar, located in Tuban Regency, in handling and preventing bullying cases within the school environment. This research employs a descriptive qualitative method, using data collection techniques such as observation, interviews with school stakeholders, and documentation. The findings indicate that SMP Negeri 3 Bancar has implemented various strategies, including the formation of an anti-bullying team, involvement of guidance and counseling teachers, regular student awareness sessions, character education reinforcement, and collaboration with parents and local authorities. The school also strives to build a positive culture through extracurricular activities and the integration of social values into learning. However, challenges such as limited resources and a lack of awareness among some students persist. This study concludes that the efforts made by SMP Negeri 3 Bancar are relatively effective in reducing bullying incidents, but continuous evaluation and support from all stakeholders are necessary to achieve a truly safe and inclusive learning environment.